2023
DOI: 10.1002/ejic.202300039
|View full text |Cite
|
Sign up to set email alerts
|

α‐Acrylaldehyde 3‐Pyrrolyl BODIPY as a Specific Optical Sensor for Cysteine and Homocysteine

Abstract: A new fluorophore, α-acrylaldehyde 3-pyrrolyl BODIPY was synthesized by treating 3-pyrrolyl BODIPY with a mixture of 3-(dimethylamino) acrolein and POCl 3 under Vilsmeier-Haack reaction conditions. The X-ray structure revealed that the fluorophore was almost planar, and the appended pyrrole was in the same plane with a small deviation from the mean plane. We investigated the potential use of α-acrylaldehyde 3-pyrrolyl BODIPY for sensing thiol containing amino acids such as cysteine/homocysteine (Cys/Hcy). Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…13 However, the synthesis of the BF 2 complex of a-pyrrolyl dipyrrin has not been thoroughly explored in previous studies due to the inaccessibility of a-pyrrolyl dipyrrin ligands. Recently, we [14][15][16][17][18][19][20][21] and others [22][23][24][25] developed a simple and facile synthetic route for BF 2 complexes of meso-aryl a-pyrrolyl dipyrrins 3a (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…13 However, the synthesis of the BF 2 complex of a-pyrrolyl dipyrrin has not been thoroughly explored in previous studies due to the inaccessibility of a-pyrrolyl dipyrrin ligands. Recently, we [14][15][16][17][18][19][20][21] and others [22][23][24][25] developed a simple and facile synthetic route for BF 2 complexes of meso-aryl a-pyrrolyl dipyrrins 3a (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…1,[8][9][10] Although, traditional approaches to prepare BODIPYs are also available, they generally require multistep processes starting from pyrrole or related unstable intermediates. 11,12 Direct C-H bond functionalization of BODIPY chromophores is a highly attractive way of exploring the diversity of the BODIPY moieties. You and Wu described a late-stage regioselective decarboxylative direct C-H arylation using substituted benzoic acids as coupling partners of BODIPY in the presence of palladium acetate, PCy 3 •HBF 4 as a ligand and silver carbonate at 140 °C for 24 h. 13 Jiao, Hao and co-workers developed a direct β-selective styrylation of BODIPYs involving the reaction of BODIPY with styrene in the presence of palladium acetate and silver acetate as an oxidant in PivOH at 80 °C.…”
Section: Introductionmentioning
confidence: 99%
“…1,8–10 Although, traditional approaches to prepare BODIPYs are also available, they generally require multistep processes starting from pyrrole or related unstable intermediates. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…There are different methods available for the synthesis of prodigiosin 1 . Interestingly, α-pyrrolyl dipyrrins readily complex with the BF 2 unit to form BF 2 -complex of α-pyrrolyl dipyrrins known as 3-pyrrolyl BODIPYs (BODIPY: 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene) which are highly fluorescent and have been used extensively as biological probes and for other applications. A few years back, we , and others reported a straightforward synthesis of meso -aryl 3-pyrrolyl BODIPYs 2 and explored their physicochemical properties. We also showed that the α-position of the appended pyrrole can be easily functionalized with functional groups such as −CHO 3 , and the functionalized meso -aryl 3-pyrrolyl BODIPYs have been used to synthesize several interesting fluorescent 3-pyrrolyl BODIPY-based conjugates .…”
Section: Introductionmentioning
confidence: 99%